Positively expansive homeomorphisms of compact spaces - David Richeson; Jim Wiseman (International Journal of Mathematics and Mathematical Sciences)
We give a new and elementary proof showing that a homeomorphism f:X→X of a compact metric space is positively expansive if and only if X is finite.